Modelling the wall collision of regular non-spherical particles and experimental validation (2014)
The importance of numerical calculations (CFD) for supporting the optimization and lay-out of industrial processes involving multiphase flows is continuously increasing. Numerous processes in powder technology involve wall-bounded gas-solid flows where wall collisions essentially affect the process performance. In modelling the particle wall-collision process in the frame of numerical computations the general assumption is that the particles are spherical. However, in most practical situations one is dealing with irregular non-spherical particles or particles with a certain shape, such as granulates or fibers. In the case of non-spherical particle-wall collisions in confined flows, additional parameters such as roughness, particle shape and orientation play an important role and may strongly affect the transport behavior. The change of linear and angular velocity of the particle depends on these parameters, specifically the orientation and the radius of impact of the particles